Designing an Urban Farming Center in Bandung City, Indonesia - June Ekawati; Aef Saepudin (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2026)
Rapid population growth and urbanization, combined with the large number of tourists visiting Bandung city, have led to a high demand for fruits and vegetables. This encourages the importance of developing an Urban Farming Center to increase food security, reduce carbon footprints, and raise awareness of environmental problems. The design of this urban farming center aims to explore the implementation of urban farming programs and provide integrated facilities that support the dissemination of urban farming practices and knowledge to the wider community—particularly in Bandung—while also contributing to the city's goal of becoming a sustainable city. The study method is a qualitative approach involving field observations and in-depth interviews at various urban farming sites, a literature review, and a studio-based design. The Urban Farming Center design process involves creative thinking in combining environmentally friendly building designs with sustainable agriculture. The theme applied to the building’s design is “Go Green Living”, while the concept is “Sustainable architecture”. The application of green building variables involves various aspects, such as the use of renewable energy sources, optimizing natural air circulation, the use of green roofs, and environmentally friendly agricultural technologies such as hydroponics, aquaponics, and efficient water management with rainwater harvesting. The design of the Urban Farming Center provides facilities such as agriculture and fisheries, education, public facilities, management facilities, service areas, and parking. This research contributes to sustainable city discourse through design solutions in enhancing urban food security, mitigating the urban heat island effect, improving energy efficiency, reducing carbon footprints, and fostering community education and participation in urban farming initiatives.